Exploration of Soil Entomopathogenic Nematodes In Peatland Oil Palm Plantations of Kubu Raya Regency - Ayen, Rosalina Yuliana; Hamdani, Hamdani (CROPSAVER, 2026)
Oil palm plantations are a major agricultural commodity in Kubu Raya Regency, West Kalimantan, and require environmentally friendly technologies to support sustainable management of pest organisms. One potential biological control agent is entomopathogenic nematodes (EPN), which are effective against soil-dwelling insect pests. This study aimed to explore and identify soil entomopathogenic nematodes and their symbiotic bacteria from peatland oil palm plantations in Kubu Raya Regency. Soil samples were collected from several oil palm plantation sites using an exploratory sampling approach. Isolation of EPN was conducted using the baiting method with Tenebrio molitor larvae as insect hosts. The experiment was arranged in a Completely Randomized Design (CRD), and data were analyzed using the Honest Significant Difference (HSD) test at a 5% significance level. The results showed that EPN were present at all sampling locations with varying population densities. The average mortality of T. molitor larvae ranged from 84% to 100%. However, statistical analysis indicated no significant differences in larval mortality among treatments (p > 0.05). In conclusion, peatland soils of oil palm plantations in Kubu Raya Regency harbor entomopathogenic nematodes with potential as biological control agents. The presence of EPN indicates their potential role in supporting sustainable agricultural systems.